Deck the halls - Whitesell, John; DeVito, Danny; Broderick, Matthew, 1962-; Davis, Kristin, 1966- (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2007)
Two neighbors compete to have the most wildly decorated house for Christmas.
Originally released as a motion picture in 2006.
Features: audio commentary, alternate/deleted scenes, interview with Dylan Blue, bloopers, behind-the-scenes featurettes.
Danny DeVito, Matthew Broderick, Kristin Davis, Kristin Chenoweth, Alia Shawkat.
MPAA rating: PG.
DVD, Dolby digital 5.1 surround.
In English, French, or Spanish with optional English or Spanish subtitles.
Keywords: Neighbors -- Drama; Christmas decorations -- Drama; Christmas plays; Fiction films; Feature films; Christmas films; Comedy films